Host-parasite interaction and morbidity in malaria endemic areas. - Marsh, K; Snow, R (1997)
Severe morbidity due to Plasmodium falciparum is a major health problem in African children. The patterns of morbidity in endemic areas are modified by the immune response, and vary markedly with transmission intensity. Severe disease falls into three overlapping syndromes: coma, respiratory distress, and severe anaemia. Recently, it has become clear that metabolic acidosis plays a major role in the pathogenesis of severe disease and is particularly important in the overlap between the different clinical syndromes. We propose that the different manifestations of severe malarial morbidity arise from the interaction of a limited number of pathogenic processes: red cell destruction, toxin-mediated activation of cytokine cascades, and infected cell sequestration in tissue microvascular beds. The pattern of severe morbidity varies with age within any one endemic area, with severe anaemia predominating in the youngest children and coma having its highest incidence in older children. Between endemic areas there is a marked variation in mean age of children with severe malaria, and therefore in the importance of different clinical syndromes. The shift in mean age is due to a combination of increased challenge and more rapid development of immunity at higher levels of transmission. Recent comparative studies indicate that at higher levels of transmission the net effect of these shifts may be a paradoxical reduction in total severe malarial morbidity.